Catastrophe of E-Commerce among Malaysian SMEs – between its perceived and proven benefits - Noor Azuan Hashim,; Nor Liza Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2014)
There is a substantial interest in the adoption of e-commerce by firms, particularly the small and medium enterprises (SMEs). SMEs are said to gain considerably from using the e-commerce because the Internet provides equal access to both SMEs and large organizations. It is also said SMEs which adopt e-commerce will improve their businesses and finally increase their profit. However, little is known concerning the benefits that SMEs have gained by adopting e-commerce and to what extent have SMEs achieved these benefits. Thus, this paper aims to analyse between the benefits that SMEs perceived they have gained and the proven benefits they realised. Survey and face-to-face interviews were carried-out in this study. The study found a number of interesting facts. Many respondents in the survey indicated that they gained some benefits, such as, more customers, increased sales, and increased productivity. Yet, the interviews did not substantiate such claims. This paper looks at these views critically and finally provides some suggestions and recommendations.